Pengaruh User Experience (UX) Design Terhadap Kemudahan Pengguna dalam Menggunakan Aplikasi TIX ID - Fadzana, Mohamad Satya; Diartono, Dwi Agus (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
In today's digital era, mobile applications have become an integral part of everyday life, including in the entertainment and online ticketing industries. This study aims to analyze the influence of User Experience (UX) design on user ease in using the Tix Id application, a popular online ticket sales platform. The research method used is a combination of descriptive analysis and case studies. Data was collected through an online survey targeting active users of the Tix Id application. The survey includes questions about UX aspects, such as navigation, interface design, responsiveness, and user satisfaction. In addition, in-depth interviews were also conducted with a number of users to gain a deeper understanding of their user experience. The research results show that UX design elements, such as an aquarium layout, easy navigation, and application responsiveness, significantly influence the user's ease in using the Tix Id application. Users who are satisfied with their experience are more likely to use an app on an ongoing basis and recommend it to others. UEQ was announced to 120 respondents, the results of the UEQ questionnaire showed that respondents had a positive impression of the TIX ID application where the application showed positive/good results. The data collection process carried out by researchers via an online questionnaire in this study was carried out for two weeks (3 October 2023 - 16 October 2023) and succeeded in obtaining 120 respondents. Respondent characteristics were collected based on gender and age, as well as frequency based on use of the TIX ID application.